A Tathwīr Kitāb Durūs al-Lughah al-'Arabiyah Juz' al-Awwal bi Dhau'i al-Mahārāt al-Lughawiyah - Ami, Fikriah Islami; Fajriyani Arsya, Fajriyani Arsya (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
Based on the objectives of learning Arabic in this institute, students are required to be more active in speaking Arabic, not only that students are also required to be proficient in listening, reading and writing in Arabic. In addition to learning Arabic today, students are required to master four skills in the Arabic language. However, judging from the background of this book, it only focuses on Arabic communication practice, while the other three skills are not presented. Based on that, the researcher wanted to develop this book